Childfree in the Qur'an: Overview of the Feminist Interpretation Paradigm - Mochammad Ikhsan; Acep Ihsan Rohmatulloh; Eni Zulaiha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explain the phenomenon of childfree from the perspective of the Qur'an, namely by referring to the books of interpretation of the Qur'an, then the discussion of childfree is re-examined using maqashid sharia (as one of the references in the Feminist interpretation paradigm). This research is included in qualitative, with descriptive analysis techniques, namely research that only explains certain conditions (in this case the interpretation of the Qur'an on childfree) without generalizing the intended research object and this research also does not use statistical analysis. The data collection technique used is library research. The author's findings, that there is no statement from the scholars of interpretation stating that childfree is an act that is contrary to Islamic law (haram), Faqihuddin Abdul Qodir said that childfree can be analogized with marriage, meaning the desire not to have children cannot be judged to the point of being haram.